Chronic widespread bodily pain is increased among individuals with history of fracture: findings from UK Biobank. Issue 1 (December 2016) - Walker-Bone, Karen; Harvey, Nicholas; Ntani, Georgia; Tinati, Tannaze; Jones, Gareth; Smith, Blair; Macfarlane, Gary; Cooper, Cyrus
Abstract Summary In this cross-sectional analysis of the UK Biobank cohort, a history of fracture was associated with increased risk of current widespread chronic pain. Purpose/Introduction We aimed to test the hypothesis that a history of fracture is associated with reporting chronic widespread bodily pain (CWBP), using baseline data from the UK Biobank cohort, comprising 502, 656 people aged 40–69 years. Methods The case definition of current chronic widespread bodily pain was based on a response of 'yes' to the question 'do you have pain all over the body?' and 'yes' to 'and have you experienced pain all over the body for more than 3 months?' Multivariable Poisson regression with robust standard errors was used to test the relationship between fracture (occurring within 5 years prior to the baseline interview, and recorded by self-report) at the spine, hip, upper limb or lower limb and CWBP, adjusting for confounders. Results Of 501, 733 participants (mean age 56.5 years), 7130 individuals reported CWBP and 23, 177 had a history of fracture affecting the upper limb, lower limb, spine and/or hip. Individuals with prior fracture were significantly more likely to report CWBP than those without. After adjustment for potential risk factors (age, gender, demographic, lifestyle and socioeconomic, and psychological), risk ratios were attenuated but remained statistically significant with a more than doubling of risk for CWBP with spine fractures in men (risk ratio (RR) 2.67, 95 % confidence interval (CI) 1.66–4.31;p < 0.001) and women (RR 2.13, 95 % CI 1.35–3.37, p = 0.001) and with hip fractures in women (RR 2.19, 95 % CI 1.33–3.59;p = 0.002). Conclusions In this cross-sectional analysis, previous fracture is associated with an increased likelihood of chronic widespread bodily pain, particularly with hip fractures in women, and spine fractures in both sexes. If replicated, these findings may help inform the identification of those most at risk of chronic widespread pain post-fracture, allowing preventative measures to be targeted.